Characterization of the Elastoplastic Response of Low Zn-Cu-Ti Alloy Sheets Using the Cpb-06 Criterion - Cruchaga-Ssa., M (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Unlike other HCP metals such as titanium and magnesium, the behavior of zinc alloyshas only been modeled in the literature. For the low Zn-Cu-Ti alloy sheet studied in this work, the anisotropy is clearly seen on the stress-strain curves and Lankford coefficients. These featuresimpose a rigorous characterization and an adequate selection of the constitutive model to obtainan accurate representation of the material behavior in metal forming simulations. To describe theelastoplastic behavior of the alloy, this paper focuses on the material characterization through theapplication of the advanced Cazacu-Plunket-Barlat 2006 (CPB-06 for short) yield function combinedwith the well-known Hollomon hardening law. To this end, a two-stage methodology is proposed. Firstly, the material characterization is performed via tensile test measurements on sheet samples cutalong the rolling, diagonal and transverse directions in order to fit the parameters involved in theassociate CPB-06/Hollomon constitutive model. Secondly, these material parameters are assessedand validated in the simulation of the bulge test using different dies. The results obtained withthe CPB-06/Hollomon model show a good agreement with the experimental data reported in theliterature. Therefore, it is concluded that this model represents a consistent approach to estimate thebehavior of Zn-Cu-Ti sheets under different forming conditions. © 2019 by the authors.
Keywords: plastic anisotropy; CPB-06 yield criterion; Zinc alloys